Monthly ICP Projection Model Using Arima Method - Handoko, Rudi (Jurnal Kajian Ekonomi dan Keuangan, 2014)
Indonesian crude oil price assumption, or commonly abbreviated as ICP plays an important role in the management of state finances. This paper aims to make an ICP projection model monthly. This paper uses econometric methods time series Box-Jenkin or ARIMA (Autoregressive Integrated Moving Average). After following the Box-Jenkin methodology, estimation results indicate that the best model to forecast the monthly ICP is ARIMA (1,2,1). Results projection ARIMA (1,2,1) with a static method is more accurate than the dynamic method with a deviation of only 0.8%. If using the static method outlook for ICP in 2014 will be in the range of US$106/bareI - US$108/barel. Policy recommendations related to the price of oil is to determine the Indonesian crude oil price assumption (ICP) suggested using ARIMA (1,2,1). The oil price models have important implications in the management of state finances, namely the ARIMA model can help establish the assumption of ICP and help respond in the event of oil price fluctuations.